Digital elevation model and orthophoto of Freya Glacier 2021 - Bernhard Hynek; Daniel Binder; Signe H Larsen (PANGAEA, 2024)
In July 2021 we surveyed the surface of Freya Glacier (Northeast Greenland). On 29th and 31st July 2021, we used a UAV (DJI Phantom 4 RTK) to obtain overlapping image series of the glacier surface. On 29th July, we photographed 80% of the glacier surface (lower part) and finished the drone flights on 31st of July. On 28th and 29th of July 2021, we surveyed ~100 mainly artificial GCPs on the glacier surface using a differential GNSS receiver and a base station. During the survey, surface ablation between 28th and 31st July was less than 0.2 m. Using a structure from motion approach, we could reconstruct 95% of the glacier surface with a very high level of detail and vertical accuracy. The DEM of the glacier has a horizontal resolution of 1m and the elevation has an RMSE at the check points of 0.18 m. The DEM and the orthofoto are projected to UTM (zone 27N, epsg:32627) and to orthometric heights (egm96). The data also contain the glacier outline of Freya Glacier in 2021 as a shapefile.